Growth or profit? Strategic orientations and long‐term performance in China - Zhou, Nan (2020)
Research summary: This study investigates the long-term performance of growth-oriented versus profit-oriented strategies in emerging markets. Theoretical justifications exist for superior performance for both types of strategic orientations, but we argue each orientation will have different implications on firms' long-term survival in emerging markets. The growth-oriented strategy faces a shortage of non-scale free resources that would limit the firm's long-term survival, while the profit-oriented strategy would improve the chance of long-term survival by developing and leveraging firm-specific advantages for sustained growth. The study also examines the moderating effects of both the level of non-scale free resources and the extent to which the economic context favors growth. The empirical testing utilizes a sample of Chinese firms during 2008–2017. Managerial summary: Emerging markets present many growth opportunities. Firms often fall into the trap of blindly pursuing these opportunities without considering internal managerial capability. This study presents the theory-based logic and empirical evidence supporting the view that the profit-oriented strategy is likely to outperform the growth-oriented strategy on a long-term basis. The growth orientation strains managerial attention that is in short supplies in emerging markets and leads to inefficiencies that cause a decline in firm performance. These results are more apparent when firms lack managerial capability and in the context of growth-inducing economic policy during an economic downturn.